1990
DOI: 10.1111/j.1365-2141.1990.tb06374.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the heterogeneity of epitopes of the platelet‐specific alloantigen, Baka

Abstract: It is well known that the platelet-specific alloantigen, Baka is carried on glycoprotein (GP) IIb, but little is known about the biochemical characteristics of its epitopes. To clarify the characteristics of the epitopes, we examined the interaction of four anti-Baka sera (Yam, Lin, Kl and MO) with their epitopes, either with or without modifications by sodium dodecyl sulphate (SDS) and/or neuraminidase. By immunoprecipitation, all four antisera bound to the intact GP IIb/IIIa complex from a Baka-positive subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…Take et al tested the hypothesis that post-translational sialylation of GP IIb affected the expression of Bak epitopes. The authors demonstrated that the binding of four anti-Bak sera to Bak changed depending on whether neuraminidase was administered to desiaylate GP IIb (64). A subsequent study by Goldberger et al, demonstrated changes in electrophoretic mobility and reactivity to antisera when Bak a and Bak b platelets were exposed to neuraminidase, thereby desiaylating GP IIb.…”
Section: Platelet Glycobiology Beyond Abo Modificationsmentioning
confidence: 99%
“…Take et al tested the hypothesis that post-translational sialylation of GP IIb affected the expression of Bak epitopes. The authors demonstrated that the binding of four anti-Bak sera to Bak changed depending on whether neuraminidase was administered to desiaylate GP IIb (64). A subsequent study by Goldberger et al, demonstrated changes in electrophoretic mobility and reactivity to antisera when Bak a and Bak b platelets were exposed to neuraminidase, thereby desiaylating GP IIb.…”
Section: Platelet Glycobiology Beyond Abo Modificationsmentioning
confidence: 99%
“…Although HPA-3a is found on GPIIb, it ap pears likely that GPIIb (or Ilb/lIIa) has a labile component (s) which is denatured after fixation, strong detergent treat ment, or prolonged storage and even reduced after extensive washing in saline (under the latter two conditions, dissocia tion of the labile component is possible). The antigenicity of HPA-3a has been found to be strongly influenced by glyco sylation, and HPA-3a antibodies from different individuals have been found to vary in their reactions with GPIIb [8,15]. However, we found that there was no obvious reduction in the reactivity after neuraminidase treatment in our case; however, we found that the reactivity was weakened after extensive washing in saline (after 6 washes), suggesting that the labile component(s) of HPA-3a may be located in the carbohydrate-rich 'fuzzy' coat (glycocalyx) which extends 15-20 nm beyond the outer surface of the lipid bilayer as observed by electron microscopic studies on the platelet membrane [16].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of HPA-3a in this report of 84% using SPRCA is close to, but slightly higher than, our previous report of 77% using MPHA [1], The difference may be due to the fact that the HPA-3a anti gen of some HPA-3a-positive platelets may only be detected when the platelets are fresh. Alternatively, population bias, heterogeneity of HPA-3a epitopes or differences in the spec ificity of different anti-HPA-3a antisera [8] could also be factors involved. Further study is needed in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in reactivity may be related to differences in the nature of these diseases. In contrast to HPA-1 epitopes [40], several studies have shown that carbohydrate residues contributed critically to the integrity of HPA-3a epitopes [49][50][51]. Djaffar et al [52] demonstrated that presence of O-linked rather than N-linked carbohydrate moieties preserves HPA-3a alloantigenic determinants.…”
Section: Heterogeneity Of Platelet-specific Alloantigenic Determinantsmentioning
confidence: 99%